2015
DOI: 10.1080/13803395.2015.1007118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen on neuronal excitability measured by critical flicker fusion frequency is dose dependent

Abstract: The effect of O2 on neuronal excitability measured by CFFF in young healthy men was dose dependent: 0.7 ATA O2 did not affect CFFF; CFFF were significantly jeopardized at 1.4 ATA O2, while CFFF recovered at 2.8 ATA. With 2.8 ATA O2, the CFFF and oxygen poisoning transduction pathways seemed to be intertwined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 39 publications
1
20
1
1
Order By: Relevance
“…Several reports have demonstrated that short-term normobaric oxygen (NBO) (maximum 1.0 ATA O2) positively influenced cognitive abilities, such as memory, visuospatial and verbal abilities (Moss and Scholey 1996;Moss et al 1998;Scholey et al 1998Scholey et al , 1999Chung et al 2006) and functional magnetic resonance (fMRI) studies have demonstrated that normobaric hyperoxia (NBO, 0.3 ATA O2) during verbal or visual tasks increases the activation of brain areas associated with cognitive processing (Choi et al 2010). Kot et al (2015) examined the effect of oxygen on neuronal excitability using CFFF in a hyperbaric environment and demonstrated a dosedependent effect. These authors concluded that neuronal excitability and oxygen poisoning transduction pathways were intertwined.…”
Section: Oxygenmentioning
confidence: 99%
“…Several reports have demonstrated that short-term normobaric oxygen (NBO) (maximum 1.0 ATA O2) positively influenced cognitive abilities, such as memory, visuospatial and verbal abilities (Moss and Scholey 1996;Moss et al 1998;Scholey et al 1998Scholey et al , 1999Chung et al 2006) and functional magnetic resonance (fMRI) studies have demonstrated that normobaric hyperoxia (NBO, 0.3 ATA O2) during verbal or visual tasks increases the activation of brain areas associated with cognitive processing (Choi et al 2010). Kot et al (2015) examined the effect of oxygen on neuronal excitability using CFFF in a hyperbaric environment and demonstrated a dosedependent effect. These authors concluded that neuronal excitability and oxygen poisoning transduction pathways were intertwined.…”
Section: Oxygenmentioning
confidence: 99%
“…According to one study, the effects on neuronal excitability measured by CFFF of changes in PO 2 could be dosedependent. 34 Oxygen at 93 kPa resulted in partial recovery of motor and memory reaction times in some hyperbaric conditions while caused incapacitation with amnesia in others. 35 In this latter study, even high PN 2 (up to 0.57 MPa) was well tolerated providing neither hypercapnia nor hyperoxia were present.…”
Section: F O R P E R S O N a L U S E O N L Ymentioning
confidence: 99%
“…The boundary between the positive and negative effects of ROS is still unclear, as oxygen metabolism in cells often induces both physiological and pathological consequences, by using intertwined transduction cellular pathways. 13 This review provides an account of the ROS studies undertaken so far in order to provide a clearer understanding. To this end, we discuss the relationship between ROS and plasticity, exposing the main cellular mechanisms responsible for pathological and physiological processes.…”
Section: Introductionmentioning
confidence: 99%